2022
DOI: 10.1007/s00520-022-07289-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the relationship between the duration of cancer and care time with the supportive care needs of patients and the quality of life of their caregivers: a path analysis

Abstract: Background Breast cancer patients face various material, and the mutual impact of patients and caregivers on each other show the need for further supportive care from the community and family. This study aimed to identify the predictors of the direct and indirect relationships of the duration of cancer and care time with the supportive needs of the patients and the quality of life of their family caregivers.Methods This descriptive-analytical study was carried out on 150 patients and their caregivers in Iran. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Sociodemographic factors such as age, gender, education status, occupation, and income, as well as cancer clinical characteristics, and different treatment strategies have previously been demonstrated to be some of the predicting factors for QoL among this population [ 3 , 5 ]. Regarding the duration of caregiving, the positive correlation between care time and caregivers’ QoL has previously been reported in a population of Iranian caregivers of breast cancer patients [ 6 ].…”
Section: Introductionmentioning
confidence: 98%
“…Sociodemographic factors such as age, gender, education status, occupation, and income, as well as cancer clinical characteristics, and different treatment strategies have previously been demonstrated to be some of the predicting factors for QoL among this population [ 3 , 5 ]. Regarding the duration of caregiving, the positive correlation between care time and caregivers’ QoL has previously been reported in a population of Iranian caregivers of breast cancer patients [ 6 ].…”
Section: Introductionmentioning
confidence: 98%
“…Qualitative studies are more widely reported, while the targeted, comprehensive and systematic assessment is rarely reported. There are few studies that focus on the needs of family caregivers at different stages of treatment (Attari et al, 2022). In this study, we focused on family caregivers of children with leukaemia, analysing all caregivers of children with ALL treated in our hospital from March to December 2020.…”
Section: Introductionmentioning
confidence: 99%